The role of pulse width manipulation compared to program changes alone for unsatisfactory sacral neuromodulation therapy: A retrospective matched‐cohort analysis. Issue 1 (11th December 2020) - Rueb, Jessica; Fascelli, Michele; Goldman, Howard B.; Vasavada, Sandip; Rackley, Raymond; Moore, Courtenay; Gill, Bradley
Abstract: Aim: Pulse width (PW) influences neuromodulation by its impact on nerve fiber recruitment. A paucity of data regarding the manipulation of PW in sacral neuromodulation (SNM) exists. This study describes the clinical features and outcomes of PW manipulation for unsatisfactory SNM therapy. Methods: A retrospective, single‐institution review was performed of reprogrammed SNM patients between 2010 and 2019. Two cohorts were created: those with PW changes ± program changes and age‐matched controls with program changes alone. Patients lacking follow‐up and non‐InterStim II models were excluded. Results: Out of 710 SNM interrogations, 147 (20.7%) had PW changes and 80 met inclusion criteria. Most PW changes were shortened (61/80, 76.3%). Clinical features did not differ between cohorts except by indication for reprogramming. The most common indication for PW change was painful stimulation (34/80, 43%), whereas in controls it was suboptimal efficacy (76/80, 95%). Clinical success was stratified by indication. There was a higher improvement in efficacy in the PW cohort (61%, 17/28 vs. 36%, 27/76, p  = .02). PW manipulation successfully relieved painful stimulation in 50% (17/34 vs. 0/3,   p  = .23), which was more likely with a shortened compared to extended PW (14/15, 93.3% vs. 0/6, 0%, p  < .01). PW resulted in improvement in localization of the stimulus in 94% (17/18 vs. 0/1, p  = .10). The subsequent lead revision or explant was significantly higher in the PW cohort (43% vs. 25%, p  = .03). Conclusion: PW manipulation may aid the salvage of unsatisfactory SNM therapy. These findings represent an initial assessment of the role of PW in SNM, particularly regarding the efficacy and painful stimuli. The further prospective investigation is warranted.